2014
DOI: 10.1371/journal.pone.0085478
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Tuberculosis Case-Finding in HIV-Positive Adults Managed at Ethiopian Health Centers: Diagnostic Yield of Xpert MTB/RIF Compared with Smear Microscopy and Liquid Culture

Abstract: BackgroundDetection of active tuberculosis (TB) before antiretroviral therapy (ART) initiation is important, but optimal diagnostic methods for use in resource-limited settings are lacking. We assessed the prevalence of TB, evaluated the diagnostic yield of Xpert MTB/RIF in comparison with smear microscopy and culture, and the impact of Xpert results on clinical management in HIV-positive adults eligible for ART at health centers in a region of Ethiopia.MethodsParticipants were prospectively recruited and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
3
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 31 publications
10
67
3
13
Order By: Relevance
“…The cohort was recruited to study methods to diagnose tuberculosis and virological failure in HIV positive adults. Detailed descriptions of the cohort has been published previously [22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…The cohort was recruited to study methods to diagnose tuberculosis and virological failure in HIV positive adults. Detailed descriptions of the cohort has been published previously [22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…Balcha et al 24 , 2014 Cinco centros de saúde localizados na Etiópia O método GeneXpert obteve bons resultados, principalmente quando comparado à baciloscopia, possuindo uma alta sensibilidade em grupos de indivíduos com avançada imunossupressão. Na opinião dos autores, o teste GeneXpert deve ser utilizado como adjunto à baciloscopia e não substituí-la, como apontam outros estudos.…”
Section: Discussionunclassified
“…Nos estudos realizados por Iram et al 18 e Tortoli et al 30 , foi constatado que esse método molecular atingiu melhores resultados, podendo substituí-la. Entretanto, Balcha et al 24 e Weyer et al 40 sugeriram que o GeneXpert seja utilizado de forma adjunta à baciloscopia. Habib et al 41 relataram que, em pacientes grávidas, o GeneXpert obteve melhor sensibilidade, detectando a doença com maior rapidez, com destaque para os casos com baciloscopia negativa.…”
Section: Discussionunclassified
“…3 Studies from high-burden HIV settings have assessed the use of Xpert as a screening tool for TB in PLHIV during routine clinical evaluations and concluded that Xpert successfully detected otherwise unrecognized TB. 4,5 Isoniazid preventive therapy (IPT) is an effective strategy for preventing progression from latent tuberculous infection to active TB disease, and has been shown to reduce severe illness and mortality in HIV-infected individuals. [6][7][8][9] Despite IPT's advantages, a number of resource-limited countries have documented suboptimal IPT coverage in PLHIV, citing reasons such as stock-outs, perceived fears of poor adherence and proliferation of isoniazid (INH) resistance, a lack of local or national commitment, and perceived difficulty of ruling out active TB.…”
Section: Increasing Isoniazid Preventive Therapy Uptake In An Hiv Promentioning
confidence: 99%